Rice bran oil deacidification by immobilized Aspergillus Niger lipase catalyzed esterification with D-isoascorbic acid. (December 2021) - Yang, Fan; Wang, Mengyang; Chao, Xinyu; Yan, Xiang; Zhang, Wencheng; Yuan, Chuanxun; Zeng, Qingmei
Graphical abstract: Highlights: D-isoascorbic acid was employed to neutralize high-acid rice bran oil. An excellent deacidification efficiency of 97.53 % was obtained. Immobilized Aspergillus Niger lipase showed high catalytic activity and stability. No more monoglycerides or diacylglycerides was accumulated in the process. The shelf life of deacidified rice bran oil was greatly improved. Abstract: The main challenge associated with the upgrading of crude rice bran oil (RBO) rests with their high content of free fatty acids (FFA). In this study, we describe a green and sustainable process for the deacidification of high-acid RBO using d -isoascorbic acid as a novel acyl acceptor in combination with a newly prepared immobilized Aspergillus Niger lipase (ANL). The process contributed a high deacidification efficiency of 97.53 % with a desirable d -isoascorbic acid ester (DIAE) content of 36.10 %. The immobilized ANL could be used consecutively for at least 10 batches with only 7.86 % of activity loss. Scale-up reaction was implemented to verify the amenability of the procedure, and a low acid value of 1.46 mg KOH/g conformed to the quality criteria of edible RBO was then obtained. Physicochemical indices analysis indicated that this procedure was amicable to bioactive phytochemicals in RBO. In addition, the Rancimat test suggested that this process greatly improved the shelf life of deacidified RBO due to the formation of DIAE. This is the first time that d -isoascorbic acid has been used in the refining of RBO. Overall, we report an economically and efficiently viable process for the upgrading of high-acid RBO.